Three-Dimensional Characterization of Trabecular Bone Mineral Density of the Distal Radius Utilizing Quantitative Computed Tomography. (January 2020) - Pidgeon, Tyler S.; DaSilva, Katia A.; Crisco, Joseph J.; Johnson, Eric C.; Chambers, Alison B.; DaSilva, Manuel F.
Background: Distal radius (DR) fractures demonstrate patterns of predictable fragments. Bone mineral density (BMD) measurements of these regions of interest (ROIs) may guide more precise treatment.Methods: Computed tomography (CT) scans of the DR of 42 healthy volunteers (23 female) were analyzed using quantitative CT software, measuring BMD within trabecular bone. Seven ROIs were described by alignment with the distal (volar ulnar distal [VUD], dorsal ulnar distal [DUD], volar radial distal [VRD], and dorsal radial distal [DRD]) or proximal (middle ulnar proximal [MUP], middle proximal [MP], and middle radial proximal [MRP]) sigmoid notch. Additional ROIs were the radial styloid (RS) and metadiaphysis (MD). A general estimation equation assessed subject's BMDs with predictive factors of gender, ROI, and age. The interaction between gender, ROI, and age was included in the model to allow for differences in ROI to vary with gender and/or age.Results: Comparing ROIs within the same gender and, separately, within the same age group revealed significantly higher BMD adjacent to the radioulnar and radiocarpal joints. Male and female individuals aged ≥50 years (mean: 172.7 mg/cm 3 ± 6.1) had significantly lower BMD than those aged <50 years (mean: 202.7 mg/cm 3 ± 5.8) when all ROIs were considered. Males had higher mean BMD at each ROI compared with females; these differences were significant in 5 of the 9 ROIs: VUD, DUD, DRD, RS, MUP.Conclusions: Trabecular BMD of the DR is highest adjacent to the radioulnar and radiocarpal joints. Female patients and those ≥50 years have lower trabecular BMD.